Analysis of FDI Determinants Using Autoregressive Distributive Lag Model: Evidence from India - R. Patel; D. R. Mohapatra; S. K. Yadav (Финансы: теория и практика, 2024)
The significance of foreign direct investment (FDI) for the expansion and advancement of emerging economies has long been recognized. Yet, research on the factors that influence FDI inflows is still developing. This study focuses on examining the long- and short-term association between FDI inflows and its determinants, employing ARDL bounds testing approach and Error Correction Model to understand the relationship between the variables under study. The findings evidence the existence long- and short-term association between FDI and domestic investment, inflation, infrastructure, and trade openness. However, market size is observed to be insignificant in influencing FDI inflows. The coefficients of domestic investment, infrastructure and Trade Openness are observed to be significantly positive. The influence of inflation is found to be negative. The study suggests that the Indian economy should accelerate the process of integration with the world economy along with the enhancement of domestic investment and infrastructure facilities to attain higher FDI.